High‐resolution chromosomal microarrays in prenatal diagnosis significantly increase diagnostic power. (21st March 2014) - Oneda, Beatrice; Baldinger, Rosa; Reissmann, Regina; Reshetnikova, Irina; Krejci, Pavel; Masood, Rahim; Ochsenbein‐Kölble, Nicole; Bartholdi, Deborah; Steindl, Katharina; Morotti, Denise; Faranda, Marzia; Baumer, Alessandra; et al.
ABSTRACT Objective The objective of this study was to determine for the first time the reliability and the diagnostic power of high‐resolution microarray testing in routine prenatal diagnostics. Methods We applied high‐resolution chromosomal microarray testing in 464 cytogenetically normal prenatal samples with any indication for invasive testing. Results High‐resolution testing revealed a diagnostic yield of 6.9% and 1.6% in cases of fetal ultrasound anomalies and cases of advanced maternal age (AMA), respectively, which is similar to previous studies using low‐resolution microarrays. In three (0.6%) additional cases with an indication of AMA, an aberration in susceptibility risk loci was detected. Moreover, one case (0.2%) showed an X‐linked aberration in a female fetus, a finding relevant for future family planning. We found the rate of cases, in which the parents had to be tested for interpretation of unreported copy number variants (3.7%), and the rate of remaining variants of unknown significance (0.4%) acceptably low. Of note, these findings did not cause termination of pregnancy after expert genetic counseling. The 0.4% rate of confined placental mosaicism was similar to that observed by conventional karyotyping and notably involved a case of placental microdeletion. Conclusion High‐resolution prenatal microarray testing is a reliable technique that increases diagnostic yield by at least 17.3% when compared with conventional karyotyping, without an increase in the frequency of variants of uncertain significance. © 2014 John Wiley & Sons, Ltd.